Therapeutic Communication In Counseling Guidance At SMAN 01 Bengkulu City (Study On Class X Science 3 Students) - Sendi Noviyanti; Sri Narti; Anis Endang (Penerbit Jurnal Indonesia, 2023)
This research aims to determine the therapeutic communication process in counseling guidance at SMAN 01 Bengkulu City. The theory used is Northouse's theory of therapeutic communication (in Suryani, 2005). This research is qualitative research in exploring data from the field, namely through in-depth interviews, direct observation and documentation. The research results stated that at the preparation stage (pre-interaction), initially before conducting counseling the teacher knew the problems the students were experiencing. Introductory stage (orientation), talk first about the problem, if it is not efficient, take it straight to the guidance room. Work stage, thinking about further understanding students' willingness to solve the problems they face. Next is the initiation stage, in counseling guidance there has been a change in the student.